Pengendalian Kualitas Ketipisan Dinding Botol Kaca Berkarbonasi Pada Proses Blow and Blow Dengan Metode Six Sigma - Abid Zaidahul Barok; Endang Pudji Purwanti; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
Non-returnable glass bottles for carbonated drinks produced by the blow and blow process have defects on the walls of the glass bottles, so that the production process is still rejected. Machine 11 had the highest reject percentage in June 2019 reached 1.20% with an average monthly reject percentage of 0.74%, this could cause harm to the company. This research aims to determine the cause of thinness of carbonated bottle walls below specifications, and also to find an effort to reduce the cause of thinness of carbonated bottle walls under specifications. The method used is Six sigma DMAIC. At the measure stage gets 4.09 sigma from the DPMO calculation and control diagram the p-chart has a statistically uncontrolled. In analyzing stage using FTA, there were 5 factors found; blank mold was replaced in productin, final blow time was too fast, counter blow time was too fast, blank mold was often repaired, swab was not done correctly, while the effort quality control to do was manually re-inject the bottles which came out of the newly replaced mold, check panel periodically during the job change process, to check final blow timing and counter blow timing, check mold lifetime, swab the dirty/ dry mold and did regular checks.